POLA PEMBINAAN DAKWAH MAHAD AL-JAMI'AH IAIN TERNATE - Amri, Muhammad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 16 No 2 (2020)DO - 10.24239/al-mishbah.Vol16.Iss2.206, 2020)
Students of Islamic institutions are required to be able to meet community expectations in the form of mastering the competence of reading and writing the koran, leading religious events and delivering da'wah to Muslims. IAIN Ternate with the Ma'had Al-Jami'ah unit in it, is demanded to be able to make efforts to guide it. This study is expected to reveal whether Ma'had IAIN Ternate conducts da'wah guidance, and what kind of guidance is carried out. This study is a field research, with a qualitative type. Sources of data obtained through observation and stakeholder interviews. Data analysis was carried out by the stages of data reduction, data presentation and data verification. In fact, Ma'had Al-Jami'ah IAIN Ternate has carried out comprehensive dakwah guidance, starting from weighting material and improving ethics through ta'lim ma'hadi activities, then equipping mahasantri with material mastery and making dakwah media, as well as doing direct practice and testing the ability of da'wah through performances at the Muhadharoh Usbu'iyah activity which was then closed with the climax event of competing the preaching skills of Mahasantri in Muhadharoh Kubra activities.